Base alteration of some heavy metal concentrations on local and seasonal in Bartin River - Özel, Handan Ucun; Özel, Halil Barış; Cetin, Mehmet; Sevik, Hakan; Gemici, Betül Tuba; Varol, Tuğrul (Springer Science and Business Media LLC, 2019)
Fresh water resources have always been an extremely invaluable economic and strategic resource in the world. There are about 1.4 billion people who have no access to pure water resources mainly due to the discharge of 95% of unpurified wastewater and 70% of industrial wastes into water resources in underdeveloped and developing countries. More than half of the world's rivers are contaminated. Eighty percent of diseases are caused by contaminated waters in developing countries. Among the pollutants in these streams, heavy metals are of particular significance, as heavy metals do not dissolve and degenerate easily in nature. They also tend to bio-accumulate. This is why determining heavy metal concentrations is of great importance because it can help detect risk zones and risk levels. This study aims to determine the alteration of some heavy metal concentrations during a year in Bartin River on a point and seasonal base. Within the scope of the study, samples were collected from 5 chosen locations on Bartin River during a year and the alteration of Cu, Fe, Zn, Mn, Ni, and Pb concentration amounts were determined monthly. As a result of the study, it was determined that there were various rates of contamination with heavy metals at all stations, and that the amount of all studied heavy metal concentrations decreased depending on seasonal alteration when precipitation and hence the flow rates were high, and the highest concentrations were calculated in samples that were collected from L3 and L5 stations. Results shows that some of the toxic metals' accumulations are higher than the suggestion of value, which recommended that the Bartin River is to some extent a toxic metal polluted river and that animals are not totally safe. Since this study constitutes a sample, all international samples should be controlled especially in the Organized Industrial Zone and foundation areas and the wastewater entering the river should be controlled and the pollution source should be determined and precautions should be taken. According to the results of the study, it also shows the water quality of the rivers in general. Pollution levels of rivers should be taken into account in the use of river water and care should be taken to use river water directly or indirectly in agricultural activities that may cause harm to human health. The results of this study can be a guide for identifying suitable areas to use the water of rivers. In future river planning, these studies will have an important guide value.
Keywords: Turkey; Heavy Metal Pollution; Agriculture; Management, Monitoring, Policy and Law; Wastewater; Pollution; Suitable Areas; Rivers; Air Pollution; Metals, Heavy; Water Quality; Water Resources; Heavy Metal Concentrations; Humans; Seasons; Water Pollutants, Chemical; Environmental Monitoring; 6. Clean water; 3. Good health; 12. Responsible consumption; 13. Climate action; 11. Sustainability